Induction of SUSD2 by STAT3 Activation Is Associated with Tumor Recurrence in HER2-Positive Breast Cancer - Yisun Jeong; Hyungjoo Kim; Daeun You; Soo Youn Cho; Sun Young Yoon; Seok Won Kim; Seok Jin Nam; Jeong Eon Lee; Sangmin Kim (Cells)
Sushi domain-containing protein 2 (SUSD2), a transmembrane protein containing a sushi motif, has been reported to have tumor-promoting functions in various types of cancer, including breast cancer. However, the regulatory mechanism of SUSD2 and its function in HER2-positive (HER2+) breast cancer have not been fully identified as yet. In this study, we explored the potential of targeting SUSD2 to overcome trastuzumab (TRZ) resistance in HER2+ breast cancer. SUSD2 expression was found to be significantly increased in HER2-overexpressing cells. Endogenous SUSD2 expression was observed in HER2+ breast cancer cells but not in estrogen receptor-positive or triple-negative breast cancer cells. We also found that SUSD2 expression was positively correlated with HER2 expression in a publicly available human primary breast cancer dataset. Although SUSD2 expression was associated with HER2, its expression levels were not affected by TRZ. Through kinase array experiments, we found that SUSD2 expression was modulated downstream of STAT3-dependent signaling in breast cancer cells overexpressing HER2. STAT3 activity was increased in EGFR+ HER2+ breast cancer cells compared to EGFR+ cells. Furthermore, we observed that SUSD2 expression was decreased by C188-9, a STAT3-specific inhibitor. Finally, we analyzed the association between patient survival and SUSD2 expression in breast cancer. Our results showed that SUSD2 expression had a negative correlation with the relapse-free survival of patients with EGFR+ HER2+ breast cancer when compared to EGFR+ breast cancer patients. Collectively, our results demonstrate that SUSD2 expression is mediated by STAT3 and imply the potential of using SUSD2 as a biomarker to stratify HER2+ breast cancer.